Thymoquinone as a Potential Adjuvant Therapy for Cancer Treatment: Evidence from Preclinical Studies - A.G.M. Mostofa; Md Kamal Hossain; Debasish Basak; Muhammad Shahdaat Bin Sayeed (Frontiers Media S.A., 2017)
Thymoquinone (TQ), the main bioactive component of Nigella sativa, has been found to exhibit anticancer effects in numerous preclinical studies. Due to its multitargeting nature, TQ interferes in a wide range of tumorigenic processes and counteracts carcinogenesis, malignant growth, invasion, migration, and angiogenesis. Moreover, TQ can specifically sensitize tumor cells toward conventional cancer treatments (e.g., radiotherapy, chemotherapy, and immunotherapy) and simultaneously minimize therapy-associated toxic effects in normal cells. In this review, we summarized the adjuvant potential of TQ as observed in various in vitro and in vivo animal models and discussed the pharmacological properties of TQ to rationalize its supplementary role in potentiating the efficacy of standard therapeutic modalities namely surgery, radiotherapy, chemotherapy, and immunotherapy. Altogether, we suggest further comprehensive evaluation of TQ in preclinical and clinical levels to delineate its implied utility as a novel complementary adjuvant therapy for cancer treatment.